The Peruvian response to the COVID-19 pandemic - Gianella Malca, Camila (United Nations University World Institute for Development Economics Research, 2022)
Why does a state like Peru, dedicated to fulfilling development goals and sustained good macroeconomic performance, appear incapable of dealing with the COVID-19 pandemic? Using the case of maternal mortality, this paper argues that the tremendous impact of the pandemic is rooted in the adoption of health policy reforms that prioritized targets, vertical programmes, and an empty understanding of health coverage over quality, the need for social change, and the strengthening of the system as a whole. This approach to health policy, dominant in Peru since the 1990s, is part of the global indicator culture of international development, which oversimplifies complex health problems such as the high number of maternal deaths, narrowing it to a focus on certain indicators without analysing their feasibility. This approach to policy-making is a form of exercising of state power and structural violence that has created a weak health system which cannot rapidly restructure and deliver remotely regular care to pregnant women in remote areas.
10.35188/UNU-WIDER/2022/212-6
Keywords: Graue Literatur; maternal mortality; targets; indicators; international development